Proportions in papilla, crestal papilla, and proximal contact area in maxillary anterior teeth: A cross-sectional study - Abhay Pandurang Kolte; Rajashri Abhay Kolte; Mukesh J Purohit; Vinisha A Bajaj (Wolters Kluwer Medknow Publications, 2022)
Background: The regeneration and maintenance of the interdental papilla presents a great challenge to the clinician while smile designing. Proportions of papilla height (PH), crestal PH (CPH), and proximal contact areas (PCA) are more stable parameters. Aim: The purpose of the present study was to evaluate and correlate the papilla proportion (PP), crestal PP (CPP), and PCA proportion (PCAP) in periodontally healthy males and females. Materials and Methods: One hundred and twenty patients in an age group of 20-40 years, divided equally based on gender, were assessed for PH, CPH, and PCA of maxillary anterior teeth. The findings were recorded on study models and radiographs to obtain the PP, CPP, and PCAP on the mesial and distal aspects of respective tooth. Statistical Analysis: The overall comparison of parameters was performed using paired t-test. Results: The mean mesial PP (43.51% ± 3.10% for male and 45.23% ± 2.23% for female) and CPP values (48.36% ± 3.35% for male and 51.16% ± 2.96% for female) were found to be greater of each tooth type and were more pronounced for females. The PCAP values were greater for distal aspects (36.76% ± 7.00% for males and 33.30% ± 6.93% for females). Conclusion: The results of the study indicate that PP and CPP are more pronounced in females, while the PCAP is more marked in males. Furthermore, it appears that the PP and CPP are inversely related to the PCAP in both males and females.